Value of MRI in medicine: More than just another test?. Issue 7 (25th August 2018) - van Beek, Edwin J.R.; Kuhl, Christiane; Anzai, Yoshimi; Desmond, Patricia; Ehman, Richard L.; Gong, Qiyong; Gold, Garry; Gulani, Vikas; Hall‐Craggs, Margaret; Leiner, Tim; Lim, C.C. Tschoyoson; Pipe, James G.; et al.
Abstract : There is increasing scrutiny from healthcare organizations towards the utility and associated costs of imaging. MRI has traditionally been used as a high‐end modality, and although shown extremely important for many types of clinical scenarios, it has been suggested as too expensive by some. This editorial will try and explain how value should be addressed and gives some insights and practical examples of how value of MRI can be increased. It requires a global effort to increase accessibility, value for money, and impact on patient management. We hope this editorial sheds some light and gives some indications of where the field may wish to address some of its research to proactively demonstrate the value of MRI. Level of Evidence : 5 Technical Efficacy : Stage 5 J. Magn. Reson. Imaging 2019;49:e14–e25.